TEACHING WITHOUT STUDENTS: EFL PRE-SERVICE TEACHERS’ EXPERIENCES TEACHING IN PANDEMIC TIME - Dwi Riyanti (STKIP Persada Khatulistiwa Sintang, 2021)
Since the outbreak of the Covid-19 pandemic, teaching and learning activities have changed dramatically. Within the Indonesian context, for example, beginning March 2020, the Indonesian government applied a social distancing policy. The situation forced both students and teachers to study and teach from home as the schools were closed to prevent the spread of the Coronavirus. This included how pre-service teachers learnt to teach. Intended to explore pre-service English teachers’ experiences related to their teaching practicum in this pandemic time, this paper focuses on gaining in-depth information related to how the research participants view their experiences during a microteaching class at an Indonesian university. The study involved six pre-service teachers who took the microteaching class. The main data were collected from pre-service teachers through written reflection and from an open-ended questionnaire. In addition, recorded videos of participants’ teaching practices were also used to triangulate the data. Data analysis was qualitatively to see the emerging themes. The findings indicates that teacher candidates in the study view their microteaching experiences as both positive and negative ways. They consider it as a positive experience as they could have high confidence in teaching. It is a negative experience because they did not have experience managingthe classroom. Despite their mixed experiences, the participants in the study still consider their teaching practice experiences to be useful in preparing their teaching practicum at schools.